Preserving hepatic artery flow during portal triad blood inflow occlusion reduces the outgrowth of hepatocarcinoma in mice after ischemia–reperfusion. Issue 12 (27th August 2013) - Shi, Bin; Li, Chong Hui; Chen, Yong Wei; Yang, Shi Zhong; Zhang, Ai Qun; Dong, Jia Hong
Abstract : Aim: To investigate the effect of different hepatic vascular occlusion maneuvers on the growth of hepatocarcinoma after liver ischemia–reperfusion (I/R) injury. Methods: A mice hepatocarcinoma model was established by portal vein injection of H22 hepatoma cells. After 3 days, the mice underwent sham operation, occlusion of portal triad (OPT), portal vein (OPV), or intermittent clamping (INT) operation. The hepatic I/R injury, pathological changes, hepatic replacement area, proliferative cell nuclear antigen expression, and extracellular signal‐regulated kinase (ERK) 1/2 activation were assessed 5 days after reperfusion. Results: Alanine aminotransferase and aspartate aminotransferase levels in the OPV group were significantly lower than those in the OPT and INT groups at 24 h after reperfusion. The hepatic injury of clamped liver lobes in the OPV group, represented by histopathological alterations and myeloperoxidase activity, was much slighter than that in the OPT and INT groups. The values of hepatic replacement area in the sham operation, OPT, OPV, and INT groups were 7.661 2.55%, 35.61 1 4.23%, 9.02 1 3.01%, and 19.95 1 4.10%, respectively. Proliferative cell nuclear antigen expression and ERK1/2 activation of tumor cells were the highest in the OPT group, and the lowest in the OPV and INT groups. Conclusion: Preserving hepatic artery flow during portal triad blood inflow occlusion substantially inhibits the outgrowth of hepatocarcinoma via attenuating hepatic I/R injury in a murine liver tumor model. These results suggest a better prevention of hepatic tumor outgrowth after hepatectomy by using the selective portal vein clamping method in liver cancer patients.